Optimising the reproducibility of measurements of the postIR IRSL signal from single-grains of K-feldspar for dating - Smedley, R. K.; Duller, G. A. T. (Ancient TL, 2013)
The reproducibility of the Risø single-grain measurement system has previously been quantified for the analysis of individual grains of quartz using the green laser and for single-grains of K-feldspar using the infrared (IR) laser at 50 °C. However, reproducibility estimates for a single-grain measurement system analysing K-feldspar grains using the post-IR IRSL (pIRIR) signal do not exist. This study provides the first measurement reproducibility estimates for both the pIRIR225 and pIRIR290 protocol using an IR laser. It is found that holding a sample at elevated temperatures (e.g. 225°C or 290°C) prior to measurement leads to loss of the pIRIR signal. The default single grain procedure implemented by the Risø reader may involve holding the sample at this elevated temperature for periods up to several hundreds of seconds, and that crucially this time may vary from one measurement to another, leading to poorer measurement reproducibility. The study demonstrates that the measurement procedure can be modified to standardise the time spent at high temperature (e.g. 290°C) and hence improve the reproducibility of the measurement system. The optimised procedure provides reproducibility estimates of 2.8 ± 0.3 % and 2.6 ± 0.3 % for the pIRIR225 and pIRIR290 signal, respectively, which are comparable to similar measurements performed with the green laser and the IR laser at 50 °C